Paternal eNOS deficiency in mice affects glucose homeostasis and liver glycogen in male offspring without inheritance of eNOS deficiency itself - Hocher, Berthold; Lu, Yong-Ping; Reichetzeder, Christoph; Zhang, Xiaoli; Tsuprykov, Oleg; Rahnenfuhrer, Jan; Xie, Li; Li, Jian; Hu, Liang; Krämer, Bernhard; Hasan, Ahmed A. (Diabetologia, 2022)
Aims/hypothesis It was shown that maternal endothelial nitric oxide synthase (eNOS) deficiency causes fatty liver disease and numerically lower fasting glucose in female wild-type offspring, suggesting that parental genetic variants may influence the offspring's phenotype via epigenetic modifications in the offspring despite the absence of a primary genetic defect. The aim of the current study was to analyse whether paternal eNOS deficiency may cause the same phenotype as seen with maternal eNOS deficiency. Methods Heterozygous (+/-) male eNOS (Nos3) knockout mice or wild-type male mice were bred with female wild-type mice. The phenotype of wild-type offspring of heterozygous male eNOS knockout mice was compared with offspring from wild-type parents. Results Global sperm DNA methylation decreased and sperm microRNA pattern altered substantially. Fasting glucose and liver glycogen storage were increased when analysing wild-type male and female offspring of +/- eNOS fathers. Wild-type male but not female offspring of +/- eNOS fathers had increased fasting insulin and increased insulin after glucose load. Analysing candidate genes for liver fat and carbohydrate metabolism revealed that the expression of genes encoding glucocorticoid receptor (Gr; also known as Nr3c1) and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (Pgc1a; also known as Ppargc1a) was increased while DNA methylation of Gr exon 1A and Pgc1a promoter was decreased in the liver of male wild-type offspring of +/- eNOS fathers. The endocrine pancreas in wild-type offspring was not affected. Conclusions/interpretation Our study suggests that paternal genetic defects such as eNOS deficiency may alter the epigenome of the sperm without transmission of the paternal genetic defect itself. In later life wild-type male offspring of +/- eNOS fathers developed increased fasting insulin and increased insulin after glucose load. These effects are associated with increased Gr and Pgc1a gene expression due to altered methylation of these genes.
Gesehen am 28.11.2023